PEMILIHAN PERUSAHAAN JASA PENGIRIMAN BARANG TERBAIK MENGGUNAKAN METODE TOPSIS - Irianto Irianto (Universitas Asahan, 2017)
Abstract - The increase in internet users throughout Indonesia has also increased the purchase of goods online. Most items purchased online use freight forwarding services. With many companies engaged in freight forwarding services, such as JNE, TIKI, POS, AND CARGO, making users get many alternatives to use freight forwarding services. Many factors influence online users in the selection of freight services, such as shipping time, price offered, services provided, to the reputation of the company. Keywords - SPK, Topsis, Freight Forwarding